READINESS FOR MOBILE LEARNING AMONG CHINESE AS A SECOND LANGUAGE LEARNERS IN A PRIVATE UNIVERSITY COLLEGE IN MALAYSIA - Jie Fang; Fong Peng Chew; Mohd Shahril Nizam Shaharom, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
Although learning Chinese as a second language (CSL) is becoming increasingly important due to the rapid development of China's comprehensive national power, CSL learning abroad faces great challenges. This study proposes to use mobile learning (m-learning), especially mobile assisted language learning (MALL), to facilitate CSL learning. This research aimed to investigate learners' readiness to engage in m-learning, their levels of mobile perception, mobile motivation, and mobile self-efficacy, as well as the correlations between these constructs. Respondents were selected using the purposive sampling method from a private university college in Melaka, Malaysia. The total number of valid cases was 95. The three instruments which were adopted to collect data in this study were examined the reliability and validity with pilot study. Descriptive analysis revealed that respondents had moderate levels of mobile perception, mobile motivation, and mobile self-efficacy. Bivariate correlation analysis revealed that all three constructs were highly correlated. Perceived usefulness (PU) ranked comparatively first, followed by perceived ease to use (PEOU) and perceived difficulty (PD). Respondents who perceived difficulty found mobile apps less useful. Respondents who perceived ease to use and usefulness were more motivated than respondents who perceived difficulty. Respondents who perceived difficulty preferred more outside help rather than relying on themselves. Respondents with moderate self-efficacy (MSE) were more motivated than respondents with high self-efficacy (HSE). In general, respondents in the higher education system have their own mobile device and are ready for m-learning. Therefore, policy makers and teachers should consider integrating m-learning and MALL into the classroom to improve formal teaching.